Novel foods: a risk profile for the house cricket (Acheta domesticus). (28th August 2018) - ,; ,; Fernandez‐Cassi, X; Supenu, A; Jansson, A; Boqvist, S; Vagsholm, I
Abstract: Novel foods could represent a sustainable alternative to traditional farming and conventional foodstuffs. Starting in 2018, Regulation (EU) 2283/2015 entered into force, laying down provisions for the approval of novel foods in Europe, including insects. This Approved Regulation establishes the requirements that enable Food Business Operators to bring new foods into the EU market, while ensuring high levels of food safety for European consumers. The present risk profile tackles the hazards for one of the most promising novel food insects, the house cricket ( Acheta domesticus ). The risk profile envisages a closed A. domesticus crickets rearing system, under Hazard Analysis and Critical Control Points (HACCP) and good farming practices (GFP), in contrast with open cricket farms. The methodology used involves screening the literature and identifying possible hazards, followed by adding relevant inclusion criteria for the evidence obtained. These criteria include animal health and food safety aspects, for the entire lifespan of crickets, based on the farm to fork One Health principle. When data were scarce, comparative evidence from close relatives of the Orthoptera genus was used (e.g. grasshoppers, locusts and other cricket species). Nevertheless, significant data gaps in animal health and food safety are present. Even if HACCP‐type systems are implemented, the risk profile identifies the following considerable concerns: (1) high total aerobic bacterial counts; (2) survival of spore‐forming bacteria following thermal processing; (3) allergenicity of insects and insect‐derived products; and (4) the bioaccumulation of heavy metals (e.g. cadmium). Other hazards like parasites, fungi, viruses, prions, antimicrobial resistance and toxins are ranked as low risk. For some hazards, a need for additional evidence is highlighted.